Microwave-assisted hydrothermal synthesis and characterization of CeO2nanowires for using as a photocatalytic material - Anukorn Phuruangrat (2018)
© 2017 Elsevier B.V. One-dimensional CeO 2 materials were successfully synthesized by a microwave assisted hypothermal method at 100, 120 and 140 °C for 30 min. Phase and morphology of the products were investigated by X-ray diffraction (XRD) and transmission electron microscopy (TEM). Their XRD patterns were specified as pure CeO 2 cubic phase. Their TEM images presented uniform CeO 2 nanorods for the synthesis temperatures of 100 °C and 120 °C and nanowires with high aspect ratio and their growth along the [1 1 0] direction for the synthesis temperature of 140 °C. The photocatalytic activities of CeO 2 samples were investigated through degradation of methyl orange (MO) as a representative dye pollutant under UV light irradiation. The CeO 2 nanowires have the highest photodegradation of 98% within 100 min.